2017
DOI: 10.1016/j.cmi.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel cosavirus species in faeces of children and its relationship with acute gastroenteritis in China

Abstract: A low prevalence of HCosV was detected, but a novel Cosavirus species was found in children with and without gastroenteritis in this study. The evidence did not support a causative role for the novel virus in paediatric AGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Summarizing, the analysis showed that the values of virus prevalence in drinking water, sewage polluted water and human blood were dependent on each other [13].…”
Section: Resultsmentioning
confidence: 97%
“…Summarizing, the analysis showed that the values of virus prevalence in drinking water, sewage polluted water and human blood were dependent on each other [13].…”
Section: Resultsmentioning
confidence: 97%
“…EVs have the highest proportion of co-infection with HCoSV followed by AdVs, RoVs, and NoVs. The high rate of co-infection with classic enteric viruses may indicate the role of these viruses in causing symptoms in patients infected with these newly discovered viruses ( 6 , 46 ). The other possible point that is against the pathologic role of these viruses in the development of GE is the low viral load in patients with GE, which might be due to transient infection and the lack of replication in the gastrointestinal tract ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human Cosavirus infection reports are still very limited worldwide, but the association of the viruses with gastroenteritis is increasing 4 , 8 , 9 . In Brazil, there is only one study considering Cosaviruses role; nevertheless its association with gastroenteritis could not be established 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Enteroviruses, polioviruses, hepatoviruses and aphthoviruses are the most exhaustively characterized animal pathogens, and are associated with a wide spectrum of clinical manifestations, including undifferentiated febrile illness, respiratory illness, aseptic meningitis and acute flaccid paralysis (AFP) 1 . Recently, metagenomics analysis made possible the identification of three new human picornaviruses: klassevirus, salivirus, and cosavirus 2 4 . The pathogenicity of Cosaviruses in humans remains unknown.…”
Section: Introductionmentioning
confidence: 99%